'Money up in smoke': The financial benefits of smoking cessation may be more motivating to people who are homeless than potential health gains. (7th April 2021) - Puljević, Cheneal; Snoswell, Aaron; Rivas, Lorena; Ali, Mohammed M.; de Greef, Wouter; Ferris, Jason; Gartner, Coral
Abstract: Introduction: High rates of tobacco smoking among people who are homeless or living in temporary accommodation exacerbate poor health outcomes and financial disadvantage. There is limited research on this population's perceptions of smoking cessation benefits or support strategies. Methods: We conducted a cross‐sectional survey of 68 male smokers living in a temporary accommodation hostel in Brisbane, Australia. The survey measured smoking and quit attempt history, perceptions of cessation aids and benefits of cessation, and awareness of the Intensive Quit Support program—a free Queensland government‐funded program comprising 12 weeks of nicotine replacement therapy supplemented with weekly calls from Quitline. Results: Participants (56% aged ≤40 years) spent a high proportion of their income on smoking (median $80/week). Although the most commonly reported perceived benefit of smoking cessation was improved health, more participants were interested in a campaign promoting the financial savings of quitting rather than the health benefits. Twice as many participants reported the high cost of smoking‐provoked thoughts of quitting than graphic health warning labels on cigarette packs (70.6% vs. 30.9%). Participants reported a high level of interest in e‐cigarettes as a cessation aid. There was a low level of awareness but moderate level of interest in the Intensive Quit Support program. Discussion and Conclusions: Smoking cessation campaigns promoting the financial savings of cessation may be more salient than health‐focused campaigns among relatively young men who smoke and experience homelessness. There is a clear need for innovative, targeted strategies promoting smoking cessation among this population.